Exploring the Challenges Faced by ESP Students in Writing Academic Essay - Rachmawati, Dwita Laksmita; Fadhilawati, Dian (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
Academic writing plays a fundamental role in both school and university settings, serving as a primary means of communication and assessment across disciplines. This research employed a qualitative approach to investigate the challenges encountered by ESP students, particularly economics students in composing English academic essays. This research was conducted in East Java, Indonesia. The qualitative component involved the documentation, semi-structured interview, and analysis of students' English essays to ascertain these obstacles and semi structured interview. There are 10 second-semester students selected as participants of this study enrolled in the Management Study Program from one private university in East Java, Indonesia during the academic year 2023/2024. The analysis of students' essay writing problems reveals several key areas of concern. These include issues with organization (writing format), task completion, originality, content and discourse, and writing mechanics. ESP students often face challenges in academic essay writing due to gaps in specialized vocabulary, grammar, and unfamiliarity with academic conventions, exacerbated by limited practice and insufficient feedback. To address these issues, educator should provide targeted language support, integrate writing-intensive courses, offer detailed feedback, and establish accessible writing resources.